2023
DOI: 10.3390/biomedicines11010224
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Potential Natural Photosensitizers in Cancer Photodynamic Therapy

Abstract: Cancer is one of the main causes of death worldwide. There are several different types of cancer recognized thus far, which can be treated by different approaches including surgery, radiotherapy, chemotherapy or a combination thereof. However, these approaches have certain drawbacks and limitations. Photodynamic therapy (PDT) is regarded as an alternative noninvasive approach for cancer treatment based on the generation of toxic oxygen (known as reactive oxygen species (ROS)) at the treatment site. PDT require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 127 publications
0
24
0
Order By: Relevance
“…31 This heavy atom functionalization of the BODIPY core on 2,6-positions was necessary to support ISC and increase singlet oxygen production. 15 After the synthesis of the starting BODIPY compounds (3)(4)(5), preparation of distyryl derivatives (6)(7)(8) was planned to produce photoactive compounds in the therapeutic perspective. The reason for choosing 3-thiophene carboxaldehyde for this reaction is that the thiophene moieties at the styryl ends of the molecule enhance the ISC activity and do not have a toxic effect.…”
Section: Molecular Design/synthesis and Characterization Of Bodipy An...mentioning
confidence: 99%
See 1 more Smart Citation
“…31 This heavy atom functionalization of the BODIPY core on 2,6-positions was necessary to support ISC and increase singlet oxygen production. 15 After the synthesis of the starting BODIPY compounds (3)(4)(5), preparation of distyryl derivatives (6)(7)(8) was planned to produce photoactive compounds in the therapeutic perspective. The reason for choosing 3-thiophene carboxaldehyde for this reaction is that the thiophene moieties at the styryl ends of the molecule enhance the ISC activity and do not have a toxic effect.…”
Section: Molecular Design/synthesis and Characterization Of Bodipy An...mentioning
confidence: 99%
“…1,2 However, non-invasive or minimally invasive alternative treatment methods are tried because of the side effects of these treatment methods including low life quality of the patients and cancer drug resistance. 3 Therefore, new treatment approaches are still required. Photodynamic therapy (PDT) could be an alternative and promising treatment modality based on a light-activated drug molecule called a photosensitizer (PS).…”
Section: Introductionmentioning
confidence: 99%
“…[12] In recent years, natural PSs and their derivatives have emerged as powerful candidates for their broad range of sources, good biocompatibility, excellent photosensitivity, as well as anti-tumor effects. [13][14][15][16] For instance, porphyrins and their derivatives (Heme, chlorophyll, chlorin e6 et al) are well studied for their outstanding 1 O 2 quantum yields. [17][18][19] Hypericin extracted from Hypericum perforatum L. can not only induce efficient PDT, but also activate strong tumor immune response.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the PSs should have good selectivity towards tumors to further reduce the phototoxicity to normal tissues during PDT [12] . In recent years, natural PSs and their derivatives have emerged as powerful candidates for their broad range of sources, good biocompatibility, excellent photosensitivity, as well as anti‐tumor effects [13–16] . For instance, porphyrins and their derivatives (Heme, chlorophyll, chlorin e6 et al.)…”
Section: Introductionmentioning
confidence: 99%
“…Currently, to overcome these complications, many studies are focusing on the coating of membranes with some bioactive materials, such as hydroxyapatite and/or alginate/chitosan, to improve both osteoinductive and antibacterial properties [ 19 , 21 ]. Photodynamic therapy has evolved through the years with developments in photosensitizers and more complex methodologies resulting in alternative treatments employed as cancer therapy [ 22 ], alleviation of autoimmune disease complications [ 23 ], and control or elimination of viral, fungal and bacterial infections in both planktonic and biofilm forms [ 24 ]. However, few studies reported the application of photodynamic treatments during GBR procedures [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%